Psychometric validation of the needs assessment tool: progressive disease in interstitial lung disease. Issue 9 (17th November 2017) - Johnson, Miriam J; Jamali, Armita; Ross, Joy; Fairhurst, Caroline; Boland, Jason; Reigada, Carla; Hart, Simon Paul; Grande, Gunn; Currow, David C; Wells, Athol U; Bajwah, Sabrina; Papadopoulos, Thanos; et al.
Abstract : The inter-rater/test–retest reliability and construct validity of a palliative care needs assessment tool in interstitial lung disease (NAT:PD-ILD) were tested using NAT:PD-ILD-guided video-recorded consultations, and NAT:PD-ILD-guided consultations, and patient and carer-report outcomes (St George's Respiratory Questionnaire (SGRQ)-ILD, Carer Strain Index (CSI)/Carer Support Needs Assessment Tool (CSNAT)). 11/16 items reached at least fair inter-rater agreement; 5 items reached at least moderate test–retest agreement. 4/6 patient constructs demonstrated agreement with SGRQ-I scores (Kendall's tau-b, 0.24–20.36; P<0.05). 4/7 carer constructs agreed with the CSI/CSNAT items (kappa, 0.23–20.53). The NAT:PD-ILD is reliable and valid. Clinical effectiveness and implementation are to be evaluated.